The magic school bus inside the Earth - Cole, Joanna; Degen, Bruce (New York : Scholastic, 1997)
On a special field trip in the magic school bus, Ms. Frizzle's class learns first hand about different kinds of rocks and the formation of the earth.
Elem. School Library Collection.
School Library Journal starred.
Wilson's Children.
3.5
K-3
Keywords: Physical geology -- Juvenile literature; Geology; Geology; Earth -- Internal structure; Earth -- Internal structure